Correlation of the Electrochemical Kinetics of High‐Salinity‐Tolerant Bioanodes with the Structure and Microbial Composition of the Biofilm. Issue 11 (12th August 2014) - Rousseau, Raphael; Santaella, Catherine; Achouak, Wafa; Godon, Jean‐Jacques; Bonnafous, Anaïs; Bergel, Alain; Délia, Marie‐Line
Abstract Increasing the conductivity of the electrolytes used in microbial electrochemical systems is an essential prerequisite to large‐scale application of these technologies. Microbial anodes formed on carbon felt from a salt marsh inoculum under polarisation at 0.1 V (versus a saturated calomel electrode), generated up to 85 A m−2 in media that contained 30–45 g L−1 of NaCl. Analyses of microbial populations showed a stringent selection of the two microbial genera Marinobacter and Desulfuromonas. Currents decreased if NaCl concentration was increased to 60 g L−1. This highest salinity was shown to consistently impact the bioanode performance in three ways: voltammetry indicated degraded electron‐transfer kinetics, confocal laser scanning microscopy showed a modified biofilm structure and DNA pyrosequencing detected a decrease in the level of Desulfuromonas spp. relative to Marinobacter spp. A consistent correlation was, thus, found between electrochemical kinetics, biofilm structure and the composition of the microbial community.